Bài 5.20 trang 202 SBT đại số và giải tích 11

Giải bài 5.20 trang 202 sách bài tập đại số và giải tích 11. Giải bất phương trình:...

Quảng cáo

Đề bài

Cho 

\(\eqalign{
& f\left( x \right) = 2{x^3} - {x^2} + \sqrt 3 ; \cr
& g\left( x \right) = {x^3} + {{{x^2}} \over 2} - \sqrt 3 . \cr} \)

Giải bất phương trình \(f'(x) > g'\left( x \right).\)

Lời giải chi tiết

\(\begin{array}{l}
f'\left( x \right) = \left( {2{x^3} - {x^2} + \sqrt 3 } \right)'\\
= 2.3{x^2} - 2x + 0 = 6{x^2} - 2x\\
g'\left( x \right) = \left( {{x^3} + \frac{{{x^2}}}{2} - \sqrt 3 } \right)'\\
= 3.{x^2} + \frac{{2x}}{2} - 0 = 3{x^2} + x\\
f'\left( x \right) > g'\left( x \right) \Leftrightarrow 6{x^2} - 2x > 3{x^2} + x\\
\Leftrightarrow 3{x^2} - 3x > 0 \Leftrightarrow 3x\left( {x - 1} \right) > 0\\
\Leftrightarrow \left[ \begin{array}{l}
x > 1\\
x < 0
\end{array} \right.
\end{array}\)

Vậy \(S=\left( { - \infty ;0} \right) \cup \left( {1; + \infty } \right).\)

Loigiaihay.com

Quảng cáo

Gửi bài